Nutritional evaluation of 3 types of novel ethanol coproducts. (27th March 2019) - Corray, S; Utterback, P; Ramchandran, D; Singh, V; Moose, S P; Parsons, C M
ABSTRACT: Five 48-h precision-fed rooster assays were conducted with the objective to determine true metabolizable energy (TMEn ) using conventional roosters and/or standardized amino acid digestibility using cecectomized roosters for distillers dried grains with solubles (DDGS) produced from human food waste at high solids content (FWDDGS), DDGS produced from 4 corn hybrids with increases in grain protein concentration or the concentrations of several dietary indispensable amino acids, and a coproduct that is produced by a process which separates a high protein and yeast fraction from ethanol stillage (Still Pro, Fluid Quip Process Technologies, Cedar Rapids, IA). These results from the first cecectomized rooster assay indicated that the standardized digestibility values for Lys, Met, Cys, Thr, and Val were 61, 75, 70, 70, and 72%, respectively. Using conventional roosters, the TMEn for the FWDDGS was 3, 890 kcal/kg DM. The DDGS produced from the high protein mutant corn hybrid had a higher protein content of 34% compared with 28% protein for DDGS from the control corn hybrid. Using Lys as an example, there was a large difference between the 2 samples; the high protein mutant DDGS contained 1.60% Lys vs 1.05% for the control DDGS. Standardized digestibility of amino acids was generally not different for the mutant DDGS and the control DDGS. Similar results were observed for Lys, Arg, and Trp for the DDGS produced from the second mutant corn hybrid. The Still Pro sample was analyzed to contain 53% protein (DM basis) with 2.22% Lys, 1.05% Met, 0.90% Cys, 2.06% Thr, and 3.08% Val. The standardized digestibility values for these amino acids were 84, 92, 87, 86, and 87%, respectively. The TMEn of the Still Pro sample was determined to be 3, 372 kcal/kg DM. In conclusion, the results of this study indicate that the nutritional value of the 3 types of novel ethanol coproducts is equal to or superior to the nutritional values generally reported for conventional DDGS.